Functional outcome of the upper limb after stroke - P. F. Blake; V. U. Fritz (AOSIS, 1996)
Is movement regained in the hemiplegic arm after stroke translated into useful function in daily activity? As no answers could be found in the literature it was decided to investigate an effective method of assessing and measuring spontaneous use of the arm, the extent to which voluntary movement correlated with spontaneous and observed use, and aspects of neurological deficit which could adversely affect upper extremity function. A test battery was drawn up and administered to seven stroke patients, all of whom had some recovery of the hemiplegic upper limb. Results of the tests indicated a generally positive correlation between motor function and spontaneous and observed use, respectively, thus fulfilling the second aim of the study. The correlation also suggests that the first aim was met and that the tests were effective in what they were designed to evaluate. Small sample size limited the conclusions which could be drawn from the results of other sub-tests. Indications were that the outcome for spontaneous use of the hemiplegic arm is poorer in patients with non-dominant hemisphere lesions. Handedness in association with dominance also appears to play a part in better outcome for dominant hemisphere lesions. In spite of the positive correlation between motor function and spontaneous use, it was felt that comprehensive evaluation of upper extremity function should be extended to include automatic use.